Alceste a bicyclette in Molierova melanholična komedija - pomladitev ali pokop - Čale Feldman, Lada (Amfiteater (Ljubljana), 2024)
The paper discusses Philippe le Guay’s film Alceste a bicyclette (2013) through the lenses of the historical controversy generated by the pressure to choose between the two main characters of Moliere’s Le Misanthrope – Alceste and Philinte – as incarnations of two radically different temperaments and moral attitudes. Besides its obvious intertextual links to the famous 17th-century piece, as well as its outstanding appreciation of the art of acting – and of the role of ageing in the acting profession – the film is, however, intriguing insofar as it not only produces but also explicitly thematises a clash between the supposed out-datedness of the classical comedy and the fact that placed in the new context, the genre nevertheless manages to reinstate its initial subversive impact.
Keywords: acting; Alceste a bicyclette; gledališče v filmu; igralstvo; Le Misanthrope; Moliere, Jean Baptiste Poquelin; slv; theatre-within-film